ANTIHYPERTENSIVE AND ANTIOXIDANT FUNCTION OF ENZYMATIC HYDROLYSATE FOR BARLEY PROLAMINE - Abadi, F. A.; Naser, J. M. (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2025)
This study was aimed to identify the role of barley prolamin (BP) hydrolysates which prepared from local barley (class Ibaa 99), prolamins isolate using pepsin and trypsin (individually - synergistically) in inhibiting the ACE 1 and as antioxidant agent. The Amino acids (AAs) content of barley protein were estimated by HPLC technique, and barley prolamin (BP) was isolated from whole barley flour (WBF) using 70% ethyl alcohol, and then purified depending IP and centrifugation. Prolamin molecular weight (M.wt) was determined using the electrophoresis technique. Barley prolamin isolate (BPI) subjected to enzymatic hydrolysis using 20U of pepsin and trypsin separately and synergistically for 8 h. Aliquot of the BPI hydrolysate was taken every 60 min to determine the degree of hydrolysis (DH%), antioxidant and antihypertensive properties. The results showed that barley protein contained 22 amino acids, and the percentage of the essential amino acids (EAA) and polar amino acids (AAs) were 35.08, 45.86 % of the barley protein composition, respectively. Prolamin constituted 24% of the total barley proteins and the BPI contained 90.5% protein. Electrophoresis pattern showed that most of the prolamin bands have M.wt about 34-55 KD. Synergistic hydrolysis of BPI gave the highest values for DH (50.68 %) after 8 h hydrolysis. The antioxidant function included the radical scavenging activity (RSA) and reducing power (RP) of hydrolysates was directly proportional to the DH%. The highest RSA value was 45% in the pepsin hydrolysates sample, and the highest absorbency for RP assay was 0.69 by synergistic hydrolysates sample after 8h. Bitter taste appeared in hydrolysates prepared by Pepsin and synergistic hydrolysis after 7h. The ACE 1 inhibition activity was proportional to the DH%, and the maximum activity reach to 81.44% after 8 h in pepsin hydrolyzed samples.